Preparation method of simulated stone using chrome-containing leather ash

By using modified chromium-containing leather ash in cement and combining cationic fixative, starch waterproofing agent and compatible agent, the problem of chromium-containing leather ash leaking in rainwater and sunlight is solved, and the simulated stone is realized Efficient preparation and environmentally friendly resource utilization.

CN116332580BActive Publication Date: 2025-02-18YANTAI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310318178.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-25
Publication Date
2025-02-18
Estimated Expiration
2043-03-25

AI Technical Summary

Technical Problem

Under long-term rainwater soaking and sunlight exposure, chromium ions and dyes are prone to leak, and traditional treatment methods are costly, making it difficult to achieve resource utilization.

Method used

By adding 12 to 18% by weight of modified chromium-containing leather ash to the cement, and fixing the free chromium complex with cationic fixative and starch waterproofing agent, the compatibility of the simulated stone surface material is improved and stability.

Benefits of technology

It effectively prevents the leakage of chromium ions and dyes, reduces the generation of hexavalent chromium ions, improves the wear resistance and compressive strength of simulated stones, and achieves resource conservation and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004150740020000181
    Figure BDA0004150740020000181
  • Figure BDA0004150740020000191
    Figure BDA0004150740020000191
  • Figure BDA0004150740020000201
    Figure BDA0004150740020000201
Patent Text Reader

Abstract

The method for preparing simulated stone by using chrome leather ash comprises the following steps: evenly mixing the dried modified chrome leather ash, a cationic fixing agent and a starch waterproofing agent, pouring the mixture into a mold, removing bubbles and smoothing the surface; removing dust, grease, mildew and algae and other adhesions on the painted surface, keeping the surface clean, dry and firm, with a wall surface moisture content of less than 10% and a pH value of less than 10; selecting a matching plastering mortar to level the wall surface, usually 2 to 3 times, applying a special putty powder, usually 2 times, grinding the surface and cleaning the floating dust; spraying the real stone surface, applying an anti-alkali sealant by brushing, and controlling the surface primer of the simulated stone to about 1 mm to obtain the simulated stone, wherein the addition of the chrome ash will not reduce the properties of the simulated stone.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an application method of chrome-containing leather ash, in particular to a preparation method of chrome-containing leather ash for preventing chromium ion leakage and used for building simulated stone. Background Art

[0002] Invention my country is the world's largest leather producer, with a total leather output of 900 million square meters, accounting for about a quarter of the world. Such a high leather production has created an annual output value of 1.3 trillion yuan and an export volume of 88.9 billion US dollars, but it has also brought huge pollution to my country's environment. In addition to wastewater pollution, solid waste pollution is also becoming a social ecological problem. The total amount of leather waste in the world is about 5 million tons, of which grinding leather ash is a type of protein solid waste containing chromium, synthetic grease, oil, tanning agent and dye generated in the leather production process. Every ton of leather processed generates about 2kg-6kg of grinding leather ash solid waste.

[0003] Chinese patent 2018102125052 provides a method for preparing functional micronized leather ash synthetic leather powder, comprising the following steps: (1) pretreatment of ground leather ash; (2) preparation of hyperbranched polymer modified leather ash; (3) blending with a negative ion releaser to prepare functional micronized leather ash. The synthetic leather wet coating powder prepared by this method enables the synthetic leather to have negative ion release, endogenous formaldehyde capture, and excellent hygienic properties. Its main disadvantage is that the preparation cost is too high and it is difficult to apply industrially.

[0004] Characterization of asphalt binder for flexible pavement modified with leather buffing ash (C.Kamaraj1, Thabiba SM.F2, SivaSankari P2, et al. Characterization of asphalt binder for flexible pavement modified with leather buffing ash, China Leather, 2018, 47(1): 35-41) was published, using chromium-containing BD (buffing ash) to make useful products, thereby reducing pollution to the environment. A new asphalt binder was developed by mixing VG-30 asphalt binder, styrene-butadiene-styrene block copolymer (SBS), warm mix additive (Sasobit) and BD in the laboratory. Super pavement asphalt binder test, rotational viscometer and dynamic shear rheometer (DSR) were used to test performance grade (PG). The test procedure followed the standard ASTM D 6373, and the new asphalt binder was named PG-88. The physical and chemical properties such as FT-IR, DSC / TGA, SEM / EDAX, rheological properties and aging were evaluated. From the DSR value, PG 88 has better anti-fatigue (G*.sinδ) and anti-rutting (G* / sinδ) performance, and it can be used as an alternative asphalt glue for asphalt pavement. Its main disadvantage is that due to market capacity restrictions, the amount of leather ash used is too small, and it cannot be used as the main choice for waste resource utilization.

[0005] The Chinese invention patent ZL 2019108571085 authorized by this team provides a method for making particle board using chrome-containing grinding leather ash, wherein the treated chrome-containing grinding leather ash, glue, nitrogen-phosphorus flame retardant, toughening agent, toughening synergist, flame retardant synthetic fatliquor, substance B and water-based transparent waterproofing agent are mixed evenly, put into a mold, heated and pressurized in a flat vulcanizer, and sprayed with substance C and isopropyl palmitate on the surface, and the particle board is obtained after curing. The obtained particle board has good flame retardancy, wear resistance and dye stability. The present invention uses a physical-chemical combination of leather scraps as particle board without destroying the material of leather ash, but the surface of the particle board is not smooth and the surface is easy to fall off due to friction for a long time, which is easy to be restricted in promotion.

[0006] The team's ZL2021103860777 involves a method for preparing foamed concrete based on the utilization of leather scraps containing chromium and coal gangue in leather making. The foamed concrete is prepared by hydrolyzing leather scraps, preparing rosin acid chloride-modified leather scraps hydrolyzate, compounding, and foaming treatment of coal gangue. The comprehensive advantage of the present invention is that leather scraps and coal gangue are completely exhausted without secondary pollution, achieving the purpose of resource utilization of waste. The present invention belongs to the hydrolysis and destruction of chromium-containing leather scraps. Relatively speaking, the hydrolysis process belongs to the most costly stage of waste resource utilization from the perspective of energy consumption and cost. Therefore, it is particularly important to find a more cost-effective way to treat waste.

[0007] From real estate to infrastructure, from domestic to foreign, from one field to the entire field, from EPC to PPP, from single enterprises to industrial towns, from sales to self-owned properties, the construction industry is shifting towards multiple industries, multiple regions, and developing more businesses.

[0008] The chrome-containing leather ash is used on the walls of buildings. This field can consume a large amount of chrome-containing leather ash. The main problem that leather ash solves in this field is that the chromium ions and dyes of the chrome-containing leather ash can be fixed under long-term immersion in rain and sunlight, and will not leak to the outside. At the same time, after long-term exposure to sunlight, a large amount of hexavalent chromium ions cannot be generated.

[0009] At present, there is no report on the research technology of using chrome-containing leather ash for building walls. Since 2006, our team has been committed to the research of chrome-containing leather scraps for a long time. We have carried out joint research on the problem of chrome-containing leather ash that has troubled leather enterprises, in order to find new channels for the application of chrome-containing leather ash. The reason why traditional chrome-containing leather ash is difficult to be studied is that the chemical hydrolysis treatment of chrome-containing leather ash contains a large amount of dyes that are difficult to remove and the cost is high. Therefore, no matter whether it is a traditional leather professional college: Sichuan University, Shaanxi University of Science and Technology, Qilu University of Technology and other universities have almost no research on this issue. Therefore, based on the dual foundation of chemistry and civil engineering, our team uses chrome-containing leather ash for building walls, hoping to find a reasonable method to provide a new channel for the resource utilization of leather ash. Summary of the invention

[0010] The present invention fixes the chromium ions in the chrome-containing leather ash. 12-18% by weight of the chrome-containing leather ash is added to cement, and the free chromium complex therein is fixed by using a cationic fixing agent and a starch waterproofing agent. The starch waterproofing agent is used to avoid or reduce the contact between water and the chrome-containing leather ash. At the same time, a compatibilizer is used to improve the compatibility of some leather scraps on the surface of the simulated stone with the anti-alkali sealing primer, thereby protecting the stability of the primer.

[0011] The invention discloses a method for preparing simulated stone by using chrome-containing leather ash, characterized in that the composition includes cement, calcium chloride, modified chrome-containing grinding leather ash, ethylhexyl palmitate, tert-butyl glycidyl carbonate, cationic fixing agent, starch waterproofing agent and anti-alkali sealing primer; the preparation method of the modified chrome-containing leather ash is as follows: 100g of chrome-containing grinding leather ash is crushed into millimeter size, then mixed evenly with 2-4g of oxalic acid and 120-130g of water, stirred and adjusted the pH to 4-4.5, 0.3-2.1g of sodium citrate dihydrate and 3-6g of chrome fixing agent are added, stirred at 45°C for 2h, continued to stir and dried to obtain modified Chromium-containing leather ash; the preparation method of the chromium fixing agent: 20g of 2-acrylamide-2-methylpropanesulfonic acid, 12-15g of ethyl acetoacetate and 10g of water are stirred and dispersed at 50-60°C, 12-25g of methacryloyloxyethyl trimethylammonium chloride, 0.6-0.9g of ethylenediaminetetraacetic acid and 400-500g of water are added in sequence, and then 2.25-2.7g of potassium persulfate initiator is added, and the reaction is stirred at 70-80°C for 1-2h, and then 1.6-2.7g of hydroxyaluminum oxalate is added, the pH value is adjusted to 7.5, the reaction is kept warm for 1-2h, and vacuum drying is performed to obtain the chromium fixing agent.

[0012] The specific method for preparing simulated stone using chrome-containing leather ash is as follows:

[0013] (1) Mix 42.5 grade cement, calcium chloride, ethylhexyl palmitate, tert-butyl glycidyl carbonate, the dried modified chrome-containing leather ash obtained in claim 1, a cationic fixative, a starch waterproofing agent and water, and stir them evenly, wherein the weight ratio of the modified chrome-containing leather ash, 42.5 grade cement, calcium chloride, ethylhexyl palmitate, tert-butyl glycidyl carbonate, a cationic fixative, a starch waterproofing agent and water is: 100: (595-775): (3-8): (1-2): (2-3): (1-2): (2-3): (800-1000), continue stirring, pour into a mold, defoam, and smooth the surface;

[0014] (2) Substrate treatment: remove dust, grease, mold, algae and other adhesions on the painted surface, keep the surface clean, dry and firm, the moisture content of the wall surface is less than 10%, and the pH value is less than 10;

[0015] (3) Wall leveling: Use matching plastering mortar to level the wall, usually 2 to 3 times, then apply special putty powder, usually 2 times, polish the surface, and clean up the dust;

[0016] (4) spraying the real stone surface in step (3), applying anti-alkali sealant by brushing, so that the surface primer of the simulated stone is controlled to 1 mm;

[0017] The composition of the anti-alkali sealing primer is: 180 parts of water, 0.6 parts of hydroxyethyl cellulose (Ashilan hydroxyethyl cellulose 250HBR, the same below), 16 parts of HYM-21 glue powder (Beijing Huanyimei HYM-21 plant glue powder, Beijing Huanyimei Polymer Research Institute, the same below); 4 parts of propylene glycol; 0.7 parts of wetting agent (Germany Corning PE-100, the same below); 2.7 parts of dispersant (China Taiwan Central Asia 5040, the same below); 2 parts of defoaming agent (Japan Nopco NXZ, the same below); 3 parts of multifunctional additives (American Dow Amp-95, the same below); 3 parts of titanium dioxide. 8 parts (Sichuan Longmang 996, the same below); 63 parts of other fillers (heavy calcium 1000 mesh, Henan Dongfang Calcium Industry Co., Ltd., the same below); 50 parts of quartz sand (120 mesh) (Hebei Lingshou County Hengcheng Colored Sand Factory); 13 parts of film-forming aid (American Eastman alcohol ester twelve film-forming aid, the same below); 260 parts of Badfu RS-308 (Guangdong Badfu Technology Co., Ltd.); 0.3 parts of penetrant (penetrant JFC-M (Jiangsu Hai'an Petrochemical Plant); 0.4-5 parts of alkali swelling thickener (Nantong Hantai Chemical Co., Ltd. thickener 935), 10-20 parts of compatibilizer;

[0018] The preparation method of the compatibilizer is as follows: 16 g of cardanol polyoxyethylene ether BGF-6 (Shanghai Bangao Chemical Co., Ltd.) and 15 g of 1,4-butanedithiol are stirred and reacted at 70-80° C. for 1-2 hours, the 1,4-butanedithiol is removed at 40° C., 6.8 g of DL-panthenol is added, the reaction is carried out at 45° C. for 30-60 minutes, 6-7 g of o-cresolphthalein is added, the reaction is carried out at 45° C. for 1-2 hours, and the pH is adjusted to 7.5 to obtain the compatibilizer.

[0019] The cationic fixative is: a. heating high-amylose corn starch milk (mass fraction 35%, pH value 6.5, the rest is water) at 65° C. and stirring for 20 hours, then adding propylene oxide with a starch content of 30% in two portions, then adding NaOH (2.5% of the dry weight of starch) and Na2SO4 (20% of water), reacting at 45° C. for 24 hours, neutralizing, filtering, washing, and drying to obtain hydroxypropyl starch;

[0020] b. Prepare 350 mL of acetate buffer (the rest is water) with 25.6 g of anhydrous sodium acetate and 11.2 mL of acetic acid, dissolve 15 g of hydroxypropyl starch in the acetate buffer at 60 ° C, add 1.3 mL of propargylamine under stirring, add sodium cyanoborohydride in 4 times, 0.3 g each time, for a total of 12 h, stir the mixture at 50 ° C for 32 h and then dialyze for 24 h. After dialysis, concentrate the solution by rotary evaporator and vacuum dry for 24 h to obtain terminal acetylene starch; first mix 20 mL of N, N-dimethylformamide with 40 mL of water, then mix 6 g of terminal acetylene starch and 260 mg of 3-Azidopropylamine was dissolved in the above mixed solution, 45 mg of copper sulfate pentahydrate and 45 mg of sodium ascorbate were added, and the solution was stirred at 80°C for 12 h. The above product was dissolved in a mixture of 20 mL of dichloromethane and 20 mL of trifluoroacetic acid, and deprotected (stirring at room temperature for 6 h under N2 conditions), and then the solution was dialyzed for 48 h and dried to obtain terminal cationic starch.

[0021] Starch waterproofing agent: Weigh 16 g of hydroxypropyl starch and 14-17 g of terminal cationic starch in claim (4) respectively, prepare a suspension with a concentration of 6% with deionized water and place it in a three-necked flask; heat and keep warm for 2 h in a constant temperature water bath at 98°C with mechanical stirring to obtain a film liquid; dissolve 3 g of hydroxy silicone oil (mass ratio of curing agent 15:1) in 50 mL of ethyl acetate and mix with the film liquid, stir and react at 70-80°C for 1-2 h, then add 6 g of water, 3-4 g of coupling agent and 0.3-0.5 g of 1-(3-chloropropoxy)-4-fluorobenzene, adjust the pH to 10, stir and react at 30-40°C for 1-2 h, and vacuum dry to obtain a starch waterproofing agent.

[0022] The coupling agents are KH550 and KH570.

[0023] The advantages of the present invention are:

[0024] (1) Since most of the chromium ions in leather tanning are single-point bound to the carboxyl group of leather, the proportion of multi-point binding is relatively low, and the stability of single-point binding is poor. After contact with water, many single-point bound chromium ions will migrate out. 201910857108.5 (the previous achievement of this team) uses oxalic acid to properly detan the leather ash, and the resulting chromium-containing liquid is concentrated and used as a tanning agent. Through detanning, the free chromium ions in the leather scraps are reduced. Since the invention of 201910857108.5 is mainly used for indoor floors, and the environment used in the present invention is outdoors, rainwater has a great effect on its chromium ion migration. Based on the previous research of the research group, the present invention modifies the chromium ion fixing agent substance A, increases the fixation of single-point bound chromium ions, and uses sodium citrate dihydrate and chromium fixing agent to fix the residual chromium ions and dyes in the leather scraps, respectively, thereby reducing the subsequent migration of chromium ions and dyes. The use of starch waterproofing agent to fix the leather ash surface in advance can prevent the migration of chromium ions. (2) The advantage of the chromium fixation is that 2-acrylamide-2-methylpropane sulfonic acid is dispersed in a system of ethyl acetoacetate and water, methacryloyloxyethyl trimethylammonium chloride is added, potassium persulfate is used as an initiator, a free radical addition reaction is carried out, and then the imino group in 2-acrylamide-2-methylpropane sulfonic acid is reacted with ethylenediaminetetraacetic acid to introduce ethylenediaminetetraacetic acid into the polymer chain, and then the hydroxysulfonate group of hydroxyaluminum oxalate and the carboxylic acid of ethylenediaminetetraacetic acid react in a weakly alkaline environment to connect ethylenediaminetetraacetic acid and hydroxyaluminum oxalate with strong complexing ability to the molecular chain, which is beneficial to the fixation of chromium, adsorption and complexing of chromium, and deposition in leather ash, thereby facilitating the fixation of chromium.

[0025] (3) The present invention designs a method for preparing terminal cationic starch, which can fix the chromium in the chromium complex in chromium-containing leather ash. If the free chromium is negative, it is also beneficial to fix the chromium.

[0026] (4) The high-amylose starch is modified by hydroxypropylation to obtain hydroxypropyl modified starch, and then an alkynyl group is introduced into the only reducing end of the starch. The cation is grafted onto the end through the "click" reaction of azide and alkyne to obtain a starch molecular chain with a positive charge at the end. The starch molecular chain is oriented during the film-forming process under the action of an external electric field, and the oriented starch film is hydrophobically modified by hydroxy silicone oil. At the same time, a coupling agent and water are used to hydrolyze it under a certain pH environment, and the excess hydroxy silicone oil is used to polymerize with the coupling agent hydrolysis product to improve the water resistance of the starch. At the same time, in order to prevent the reaction rate of the coupling agent hydrolysis product with the polyhydroxy silicone oil, 1-(3-chloropropoxy)-4-fluorobenzene is used to retard the reaction rate, so that the waterproofing agent is controllable and will not explode seriously.

[0027] (5) The purpose of the compatibilizer is to solve the compatibility between the simulated stone surface (cement, leather ash) and the primer. The present invention adopts the double bond contained in the cardanol polyoxyethylene ether and the two hydrogens in 1,4-butanedithiol to add under a heating environment to generate an intermediate of terminal hydroxyl group and thiol group, and then the intermediate is modified by polyhydroxy DL-panthenol to react with the thiol group, and then o-cresolphthalein with strong chromium complexing ability is used to react with the hydroxyl group of DL-panthenol, and finally the pH is adjusted to 7.5 to control the phenolic hydroxyl group in o-cresolphthalein to be in a salt environment, so that the obtained compatibilizer can be complexed with free chromium ions or combined with chromium complexes, protein carboxyl groups and amino groups in leather ash, so that cement, leather ash and primer can achieve compatibility, and at the same time, the free chromium ions are also properly fixed.

[0028] (6) Hydroxy aluminum oxalate is obtained from Example 1 of invention patent 200410000109.1. The raw materials involved in the present invention do not specify the enterprise, and the main and core raw materials can achieve the above functions. DETAILED DESCRIPTION

[0029] Example 1

[0030] The preparation method of modified chrome-containing leather ash is as follows: 100g of chrome-containing grinding leather ash is crushed into millimeter size, then mixed evenly with 2g of oxalic acid and 120g of water, stirred and adjusted to pH 4-4.5, 0.3g of sodium citrate dihydrate and 3g of chromium fixing agent are added, stirred at 45°C for 2h, and dried after continued stirring to obtain modified chrome-containing leather ash; the preparation method of the chromium fixing agent is as follows: 20g of 2-acrylamide-2-methylpropanesulfonic acid, 12g of ethyl acetoacetate and 10g of water are stirred and dispersed at 50°C, 12g of methacryloyloxyethyl trimethylammonium chloride, 0.6g of ethylenediaminetetraacetic acid and 400g of water are added in sequence, and then 2.25g of potassium persulfate initiator (10g dissolved in water, the same below) is added, and the reaction is stirred at 70°C for 1h, and then 1.6g of hydroxyaluminum oxalate is added, and the pH value is adjusted to 7.5, the reaction is kept warm for 1h, and vacuum dried to obtain the chromium fixing agent.

[0031] The specific method for preparing simulated stone using chrome-containing leather ash is as follows:

[0032] (1) Mix 42.5 grade cement, calcium chloride, ethylhexyl palmitate, tert-butyl glycidyl carbonate, the dried modified chrome-containing leather ash obtained in claim 1, a cationic fixative, a starch waterproofing agent and water, and stir them evenly, wherein the weight ratio of the modified chrome-containing leather ash, 42.5 grade cement, calcium chloride, ethylhexyl palmitate, tert-butyl glycidyl carbonate, a cationic fixative, a starch waterproofing agent and water is 100:595:3:1:2:1:2:800, continue stirring, pour into a mold, defoam, and smooth the surface;

[0033] (2) Substrate treatment: remove dust, grease, mold, algae and other adhesions on the painted surface, keep the surface clean, dry and firm, the moisture content of the wall surface is less than 10%, and the pH value is less than 10;

[0034] (3) Wall leveling: Use matching plastering mortar to level the wall, usually 2 to 3 times, then apply special putty powder, usually 2 times, polish the surface, and clean up the dust;

[0035] (4) spraying the real stone surface in step (3), applying anti-alkali sealant by brushing, so that the surface primer of the simulated stone is controlled to 1 mm;

[0036] The composition of the anti-alkali sealing primer is: 180 parts of water, 0.6 parts of hydroxyethyl cellulose (Ashilan hydroxyethyl cellulose 250HBR, the same below), 16 parts of HYM-21 glue powder (Beijing Huanyimei HYM-21 plant glue powder, Beijing Huanyimei Polymer Research Institute, the same below); 4 parts of propylene glycol; 0.7 parts of wetting agent (German Koning PE-100, the same below); 2.7 parts of dispersant (China Taiwan Zhongya 5040, the same below); 2 parts of defoaming agent (Japan Nopco NXZ, the same below); 3 parts of multifunctional additives (American Dow Amp-95, the same below); titanium 38 parts of white powder (Sichuan Longmang 996, the same below); 63 parts of other fillers (heavy calcium 1000 mesh, Henan Dongfang Calcium Industry Co., Ltd., the same below); 50 parts of quartz sand (120 mesh, Hebei Lingshou County Hengcheng Colored Sand Factory); 13 parts of film-forming aid (American Eastman alcohol ester twelve film-forming aid, the same below); 260 parts of Badfu RS-308 (Guangdong Badfu Technology Co., Ltd.); 0.3 parts of penetrant (penetrant JFC-M (Jiangsu Hai'an Petrochemical Plant); 0.4 parts of alkali swelling thickener (Nantong Hantai Chemical Co., Ltd. thickener 935), 10 parts of compatibilizer;

[0037] The preparation method of the compatibilizer is as follows: 16 g of cardanol polyoxyethylene ether BGF-6 (Shanghai Bangao Chemical Co., Ltd.) and 15 g of 1,4-butanedithiol are stirred and reacted at 70° C. for 1 hour, the temperature is lowered by 40° C., 6.8 g of DL-panthenol is added, the reaction is carried out at 45° C. for 30 minutes, 6 g of o-cresolphthalein is added, the reaction is carried out at 45° C. for 1 hour, and the pH is adjusted to 7.5 to obtain the compatibilizer.

[0038] The cationic fixative is: a. heating high-amylose corn starch milk (mass fraction 35%, pH value 6.5, the rest is water) at 65° C. and stirring for 20 hours, then adding propylene oxide with a starch content of 30% in two portions, then adding NaOH (2.5% of the dry weight of starch) and Na2SO4 (20% of water), reacting at 45° C. for 24 hours, neutralizing, filtering, washing, and drying to obtain hydroxypropyl starch;

[0039] b. Prepare 350 mL of acetate buffer (the rest is water) with 25.6 g of anhydrous sodium acetate and 11.2 mL of acetic acid, dissolve 15 g of hydroxypropyl starch in the acetate buffer at 60° C., add 1.3 mL of propargylamine under stirring, add sodium cyanoborohydride in 4 portions, 0.3 g each time, with an interval of 1 hour each time, and react for 12 hours (the same below), stir the mixture at 50° C. for 32 hours, then dialyze for 24 hours, concentrate the solution by rotary evaporator after dialysis, and vacuum dry for 24 hours to obtain terminal acetylene starch; first Mix 20 mL of N,N-dimethylformamide with 40 mL of water, then dissolve 6 g of terminal acetyl starch and 260 mg of 3-azidopropylamine in the mixed solution, add 45 mg of copper sulfate pentahydrate and 45 mg of sodium ascorbate, and stir the solution at 80 ° C for 12 h. Dissolve the above product in a mixture of 20 mL of dichloromethane and 20 mL of trifluoroacetic acid, deprotect (continue stirring at room temperature for 6 h under N2 conditions), and then dialyze the solution for 48 h and dry it to obtain terminal cationic starch.

[0040] Starch waterproofing agent: Weigh 16 g of the above-mentioned hydroxypropyl starch and 14 g of terminal cationic starch respectively, prepare a suspension with a concentration of 6% with deionized water and place it in a three-necked flask; heat and keep warm for 2 hours in a constant temperature water bath at 98°C with mechanical stirring to obtain a membrane liquid; dissolve 3 g of hydroxy silicone oil (mass ratio of diethylenetriamine curing agent 15:1, less curing amount, the same below) in 50 mL of ethyl acetate and mix with the membrane liquid, stir and react at 70°C for 1 hour, then add 6 g of water, 3 g of coupling agent KH550 and 0.3 g of 1-(3-chloropropoxy)-4-fluorobenzene, adjust the pH to 10, stir and react at 30°C for 1 hour, and vacuum dry to obtain a starch waterproofing agent.

[0041] Example 2

[0042] The preparation method of modified chrome-containing leather ash is as follows: 100g of chrome-containing grinding leather ash is crushed into millimeter size, then mixed evenly with 4g of oxalic acid and 130g of water, stirred and adjusted to pH 4-4.5, 2.1g of sodium citrate dihydrate and 6g of chromium fixing agent are added, stirred at 45°C for 2h, and then dried after continued stirring to obtain modified chrome-containing leather ash; the preparation method of the chromium fixing agent is as follows: 20g of 2-acrylamide-2-methylpropanesulfonic acid, 15g of ethyl acetoacetate and 10g of water are stirred and dispersed at 60°C, 25g of methacryloyloxyethyl trimethylammonium chloride, 0.9g of ethylenediaminetetraacetic acid and 500g of water are added in sequence, and then 2.7g of potassium persulfate initiator is added, and the reaction is stirred at 80°C for 2h, and then 2.7g of hydroxyaluminum oxalate is added, the pH value is adjusted to 7.5, the reaction is kept warm for 2h, and vacuum dried to obtain the chromium fixing agent.

[0043] The specific method for preparing simulated stone using chrome-containing leather ash is as follows:

[0044] (1) The weight ratio of modified chrome leather ash, 42.5 grade cement, calcium chloride, ethylhexyl palmitate, tert-butyl glycidyl carbonate, cationic fixative, starch waterproofing agent and water is 100:775:8:2:3:2:3:1000, stir evenly, pour into a mold, defoam, and smooth the surface;

[0045] (2) Substrate treatment: remove dust, grease, mold, algae and other adhesions on the painted surface, keep the surface clean, dry and firm, the moisture content of the wall surface is less than 10%, and the pH value is less than 10;

[0046] (3) Wall leveling: Use matching plastering mortar to level the wall, usually 2 to 3 times, then apply special putty powder, usually 2 times, polish the surface, and clean up the dust;

[0047] (4) spraying the real stone surface in step (3), applying anti-alkali sealant by brushing, so that the surface primer of the simulated stone is controlled to 1 mm;

[0048] The composition of the anti-alkali sealing primer is: 180 parts of water, 0.6 parts of hydroxyethyl cellulose (Ashilan hydroxyethyl cellulose 250HBR, the same below), 16 parts of HYM-21 glue powder (Beijing Huanyimei HYM-21 plant glue powder, Beijing Huanyimei Polymer Research Institute, the same below); 4 parts of propylene glycol; 0.7 parts of wetting agent (German Koning PE-100, the same below); 2.7 parts of dispersant (China Taiwan Zhongya 5040, the same below); 2 parts of defoaming agent (Japan Nopco NXZ, the same below); 3 parts of multifunctional additives (American Dow Amp-95, the same below); 38 parts of titanium dioxide (Sichuan Longmang 996, the same below); 63 parts of other fillers (heavy calcium 1000 mesh, Henan Dongfang Calcium Industry Co., Ltd., the same below); 50 parts of quartz sand (120 mesh) (Hebei Lingshou County Hengcheng Colored Sand Factory); 13 parts of film-forming aid (American Eastman alcohol ester twelve film-forming aid, the same below); 260 parts of Badfu RS-3082 (Guangdong Badfu Technology Co., Ltd.); 0.3 parts of penetrant (penetrant JFC-M (Jiangsu Hai'an Petrochemical Plant); 5 parts of alkali swelling thickener (Nantong Hantai Chemical Co., Ltd. thickener 935), 20 parts of compatibilizer;

[0049] The preparation method of the compatibilizer is as follows: 16 g of cardanol polyoxyethylene ether BGF-6 (Shanghai Bangao Chemical Co., Ltd.) and 15 g of 1,4-butanedithiol are stirred and reacted at 80° C. for 2 hours, the temperature is lowered by 40° C., 6.8 g of DL-panthenol is added, the reaction is carried out at 45° C. for 60 minutes, 7 g of o-cresolphthalein is added, the reaction is carried out at 45° C. for 2 hours, and the pH is adjusted to 7.5 to obtain the compatibilizer.

[0050] The cationic fixative is: a. heating high-amylose corn starch milk (mass fraction 35%, pH value 6.5, the rest is water) at 65° C. and stirring for 20 hours, then adding propylene oxide with a starch content of 30% in two portions, then adding NaOH (2.5% of the dry weight of starch) and Na2SO4 (20% of water), reacting at 45° C. for 24 hours, neutralizing, filtering, washing, and drying to obtain hydroxypropyl starch;

[0051] b. Prepare 350 mL of acetate buffer (the rest is water) with 25.6 g of anhydrous sodium acetate and 11.2 mL of acetic acid, dissolve 15 g of hydroxypropyl starch in acetate buffer at 60 ° C, add 1.3 mL of propargylamine under stirring, add sodium cyanoborohydride in 4 times, 0.3 g each time, with an interval of 1 hour each time, and react for 12 hours (the same below), stir the mixture at 50 ° C for 32 hours, then dialyze for 24 hours, concentrate the solution by rotary evaporator after dialysis, and vacuum dry for 24 hours to obtain terminal acetylene starch; first Mix 20 mL of N,N-dimethylformamide with 40 mL of water, then dissolve 6 g of terminal acetyl starch and 260 mg of 3-azidopropylamine in the mixed solution, add 45 mg of copper sulfate pentahydrate and 45 mg of sodium ascorbate, and stir the solution at 80 ° C for 12 h. Dissolve the above product in a mixture of 20 mL of dichloromethane and 20 mL of trifluoroacetic acid, deprotect (continue stirring at room temperature for 6 h under N2 conditions), and then dialyze the solution for 48 h and dry it to obtain terminal cationic starch.

[0052] Starch waterproofing agent: Weigh 16 g of the hydroxypropyl starch and 17 g of the terminal cationic starch prepared above, respectively, prepare a suspension with a concentration of 6% with deionized water and place it in a three-necked flask; heat and keep warm for 2 hours in a constant temperature water bath at 98°C with mechanical stirring to obtain a membrane liquid; dissolve 3 g of hydroxy silicone oil (mass ratio of diethylenetriamine curing agent 15:1, less curing amount, the same below) in 50 mL of ethyl acetate and mix with the membrane liquid, stir and react at 80°C for 2 hours, then add 6 g of water, 4 g of KH570 coupling agent and 0.5 g of 1-(3-chloropropoxy)-4-fluorobenzene, adjust the pH to 10, stir and react at 40°C for 2 hours, and vacuum dry to obtain a starch waterproofing agent.

[0053] Example 3

[0054] The preparation method of the modified chrome-containing leather ash is as follows: 100 g of chrome-containing leather ash is crushed into millimeter size, then mixed evenly with 3 g of oxalic acid and 125 g of water, stirred and adjusted to pH 4-4.5, 1.2 g of sodium citrate dihydrate and 4.5 g of chrome fixing agent are added, stirred at 45° C. for 2 h, continued to stir and then dried to obtain the modified chrome-containing leather ash;

[0055] The preparation method of the chromium fixing agent is as follows: 20g of 2-acrylamide-2-methylpropanesulfonic acid, 13.5g of ethyl acetoacetate and 10g of water are stirred and dispersed at 55°C, 18.5g of methacryloyloxyethyl trimethylammonium chloride, 0.75g of ethylenediaminetetraacetic acid and 450g of water are added in sequence, and then 2.5g of potassium persulfate initiator is added, and the mixture is stirred and reacted at 75°C for 1.5h, and then 2.1g of hydroxyaluminum oxalate is added, the pH value thereof is adjusted to 7.5, the mixture is kept warm for reaction for 1.5h, and vacuum dried to obtain the chromium fixing agent.

[0056] The specific method for preparing simulated stone using chrome-containing leather ash is as follows:

[0057] (1) Mix the modified chrome leather ash, 42.5 grade cement, calcium chloride, ethylhexyl palmitate, tert-butyl glycidyl carbonate, cationic fixative, starch waterproofing agent and water in a weight ratio of 100:680:5.5:1.5:2.5:1.5:2.5:900, stir evenly, pour into a mold, defoam, and smooth the surface;

[0058] (2) Substrate treatment: remove dust, grease, mold, algae and other adhesions on the painted surface, keep the surface clean, dry and firm, the moisture content of the wall surface is less than 10%, and the pH value is less than 10;

[0059] (3) Wall leveling: Use matching plastering mortar to level the wall, usually 2 to 3 times, then apply special putty powder, usually 2 times, polish the surface, and clean up the dust;

[0060] (4) spraying the real stone surface in step (3), applying anti-alkali sealant by brushing, so that the surface primer of the simulated stone is controlled to 1 mm;

[0061] The composition of the anti-alkali sealing primer is: 180 parts of water, 0.6 parts of hydroxyethyl cellulose (Ashilan hydroxyethyl cellulose 250HBR, the same below), 16 parts of HYM-21 glue powder (Beijing Huanyimei HYM-21 plant glue powder, Beijing Huanyimei Polymer Research Institute, the same below); 4 parts of propylene glycol; 0.7 parts of wetting agent (German Koning PE-100, the same below); 2.7 parts of dispersant (China Taiwan Zhongya 5040, the same below); 2 parts of defoaming agent (Japan Nopco NXZ, the same below); 3 parts of multifunctional additives (American Dow Amp-95, the same below); titanium 38 parts of white powder (Sichuan Longmang 996, the same below); 63 parts of other fillers (heavy calcium 1000 mesh, Henan Dongfang Calcium Industry Co., Ltd., the same below); 50 parts of quartz sand (120 mesh) (Hebei Lingshou County Hengcheng Colored Sand Factory); 13 parts of film-forming aid (American Eastman alcohol ester twelve film-forming aid, the same below); 260 parts of Badfu RS-308 (Guangdong Badfu Technology Co., Ltd.); 0.3 parts of penetrant (penetrant JFC-M (Jiangsu Hai'an Petrochemical Plant); 2.7 parts of alkali swelling thickener (Nantong Hantai Chemical Co., Ltd. thickener 935), 15 parts of compatibilizer;

[0062] The preparation method of the compatibilizer is as follows: 16 g of cardanol polyoxyethylene ether BGF-6 (Shanghai Bangao Chemical Co., Ltd.) and 15 g of 1,4-butanedithiol are stirred and reacted at 75°C for 1.5 hours, the temperature is reduced by 40°C, 6.8 g of DL-panthenol is added, the reaction is carried out at 45°C for 45 minutes, 6.5 g of o-cresolphthalein is added, the reaction is carried out at 45°C for 1.5 hours, and the pH is adjusted to 7.5 to obtain the compatibilizer.

[0063] The cationic fixative is: a. heating high-amylose corn starch milk (mass fraction 35%, pH value 6.5, the rest is water) at 65° C. and stirring for 20 hours, then adding propylene oxide with a starch content of 30% in two portions, then adding NaOH (2.5% of the dry weight of starch) and Na2SO4 (20% of water), reacting at 45° C. for 24 hours, neutralizing, filtering, washing, and drying to obtain hydroxypropyl starch;

[0064] b. 25.6 g of anhydrous sodium acetate and 11.2 mL of acetic acid were used to prepare 350 mL of acetate buffer (the rest was water), 15 g of hydroxypropyl starch was dissolved in acetate buffer at 60 ° C, 1.3 mL of propargylamine was added under stirring, sodium cyanoborohydride was added in 4 times, 0.3 g each time, 1 h interval between each time, and the reaction was 12 h (the same below), the mixture was stirred at 50 ° C for 32 h and then dialyzed for 24 h. After dialysis, the solution was concentrated by rotary evaporator and vacuum dried for 24 h to obtain terminal acetylene starch; first, 20 mL of N, N-dimethylformamide was mixed with 40 mL of water, and then 6 g of terminal acetylene starch and 260 mg 3-Azidopropylamine was dissolved in the above mixed solution, 45 mg of copper sulfate pentahydrate and 45 mg of sodium ascorbate were added, and the solution was stirred at 80°C for 12 h. The above product was dissolved in a mixture of 20 mL of dichloromethane and 20 mL of trifluoroacetic acid, and deprotected (stirring at room temperature for 6 h under N2 conditions), and then the solution was dialyzed for 48 h and dried to obtain terminal cationic starch.

[0065] Starch waterproofing agent: 16 g of the above-mentioned hydroxypropyl starch and 15.5 g of terminal cationic starch are prepared into a 6% suspension with deionized water and placed in a three-necked flask; the suspension is heated and kept warm for 2 h in a constant temperature water bath at 98°C with mechanical stirring to obtain a membrane liquid; 3 g of hydroxy silicone oil (mass ratio of diethylenetriamine curing agent is 15:1, less curing amount, the same below) is dissolved in 50 mL of ethyl acetate and mixed with the membrane liquid, stirred and reacted at 75°C for 1.5 h, and then 6 g of water, 3.5 g of KH550 coupling agent and 0.4 g of 1-(3-chloropropoxy)-4-fluorobenzene are added, the pH is adjusted to 10, stirred and reacted at 35°C for 1.5 h, and vacuum dried to obtain a starch waterproofing agent.

[0066] The peel strength was measured using the Zhongye Jingke HTS-BLY2510 fully computer-controlled peel strength tester.

[0067] Table 1 Primer peel strength

[0068]

[0069] The comparative example uses the simulated stone surface of the real stone paint of Example 1 of 2019110496650, and is retested in the same environment (different from its experimental data). From the primer peeling strength in Table 1, it can be found that the compatibilizer, o-cresolphthalein, and DL-panthenol play a role in improving the compatibility between the primer and the simulated stone surface.

[0070] The prepared simulated stone was immersed in 100 ml of water for 96 h, and the Cr concentration was measured by atomic absorption spectrometer.

[0071] Table 2 Chromium ion concentration

[0072]

[0073] It can be found from Table 2 that chromium fixing agent, aluminum hydroxyoxalate, ethylenediaminetetraacetic acid, cationic fixing agent and starch waterproofing agent all have an impact on the concentration of water-washed chromium ions. The experiment found that when the real stone surface was exposed to sunlight for 96 hours and immersed in water for 96 hours, no hexavalent chromium at the ppm level was found.

[0074] The compressive strength is tested in accordance with JC 79-92 Natural Marble Building Board and GB / T9966.1-2020 Natural Stone Test Method; the sample thickness is controlled at 50mm.

[0075] Table 3 Compressive strength

[0076]

[0077] From Table 3, it can be found that the addition of modified chrome ash will reduce the compressive strength of real stone, but the decline is controllable and can meet the standard requirement of JC 79-92 natural marble building panels exceeding 20Mpa.

Claims

1. A method for preparing simulated stone using chrome-containing leather ash, characterized in that: Its composition includes cement, calcium chloride, modified chrome-containing emery leather ash, ethylhexyl palmitate, glycidyl tert-carbonate, cationic fixative, starch waterproofing agent and alkali-resistant sealing primer; The preparation method of the modified chromium-containing grinding leather ash is as follows: 100 g of chromium-containing grinding leather ash is crushed into millimeter size, then mixed evenly with 2-4 g of oxalic acid and 120-130 g of water, stirred and adjusted to pH 4-4.5, 0.3-2.1 g of sodium citrate dihydrate and 3-6 g of chromium fixing agent are added, stirred at 45° C. for 2 h, continued to stir and then dried to obtain the modified chromium-containing grinding leather ash; The preparation method of the chromium fixing agent is as follows: 20g of 2-acrylamide-2-methylpropanesulfonic acid, 12-15g of ethyl acetoacetate and 10g of water are stirred and dispersed at 50-60°C, 12-25g of methacryloyloxyethyl trimethylammonium chloride, 0.6-0.9g of ethylenediaminetetraacetic acid and 400-500g of water are added in sequence, and then 2.25-2.7g of potassium persulfate initiator is added, and the mixture is stirred and reacted at 70-80°C for 1-2h, and then 1.6-2.7g of hydroxyaluminum oxalate is added, the pH value thereof is adjusted to 7.5, the mixture is kept warm for reaction for 1-2h, and vacuum dried to obtain the chromium fixing agent; The preparation method of the simulated stone using chrome-containing leather ash is as follows: (1) Mix 42.5 grade cement, calcium chloride, ethylhexyl palmitate, tert-butyl glycidyl carbonate, modified chrome-containing milled leather ash, cationic fixative, starch waterproofing agent and water, and mix them evenly. The weight ratio of modified chrome-containing milled leather ash, 42.5 grade cement, calcium chloride, ethylhexyl palmitate, tert-butyl glycidyl carbonate, cationic fixative, starch waterproofing agent and water is: 100: (595-775): (3-8): (1-2): (2-3): (1-2): (2-3): (800-1000). Continue mixing, pour into a mold, defoam, and smooth the surface. (2) Substrate treatment: remove dust, grease, mold, algae and other adherents on the surface to be painted, keep the surface clean, dry and firm, the moisture content of the wall surface is less than 10%, and the pH value is less than 10; (3) Wall leveling: Use matching plastering mortar to level the wall for 2 to 3 times, then apply special putty powder 2 times, polish the surface, and clean up the dust; (4) spraying and applying alkali-resistant sealing primer on the simulated stone surface in step (3) to control the thickness of the primer on the simulated stone surface to 1 mm; The composition of the alkali-resistant sealing primer is: 180 parts of water, 0.6 parts of hydroxyethyl cellulose, 16 parts of HYM-21 rubber powder; 4 parts of propylene glycol; 0.7 parts of wetting agent; 2.7 parts of dispersant; 2 parts of defoaming agent; 3 parts of multifunctional additives; 38 parts of titanium dioxide; 63 parts of other fillers; 50 parts of 120 mesh quartz sand; 13 parts of film-forming additives; 260 parts of Badfu RS-308; 0.3 parts of penetrant JFC-M; 0.4~5 parts of alkali swelling thickener, and 10~20 parts of compatibilizer.

2. The method for preparing simulated stone using chrome-containing leather ash as claimed in claim 1, wherein the preparation method of the compatibilizer is as follows: 16 g of cardanol polyoxyethylene ether BGF-6 and 15 g of 1,4-butanedithiol are stirred for reaction at 70-80°C for 1-2 h, the 1,4-butanedithiol is removed at 40°C, 6-8 g of DL-panthenol is added, the reaction is carried out at 45°C for 30-60 min, 6-7 g of o-cresolphthalein is added, the reaction is carried out at 45°C for 1-2 h, and the pH is adjusted to 7.5 to obtain the compatibilizer.

3. The method for preparing simulated stone using chrome leather ash as claimed in claim 1, wherein the cationic fixing agent is: a. heating and stirring a high-amylose corn starch milk with a mass fraction of 35%, a pH value of 6.5, and the rest being water at 65°C for 20 h, then adding propylene oxide with a starch content of 30% in two portions, then adding 2.5% NaOH with a dry weight of starch and 20% Na2SO4 with a water weight, reacting at 45°C for 24 h, neutralizing, filtering, washing, and drying to obtain hydroxypropyl starch; b. 25.6 g of anhydrous sodium acetate and 11.2 mL of acetic acid were used to prepare 350 mL of acetate buffer with water as solvent. 15 g of hydroxypropyl starch was dissolved in acetate buffer at 60 °C. 1.3 mL of propargylamine was added under stirring. Sodium cyanoborohydride was added in 4 portions, 0.3 g each time, for a total of 12 h. The mixture was stirred at 50 °C for 32 h and then dialyzed for 24 h. After dialysis, the solution was concentrated by rotary evaporator and vacuum dried for 24 h to obtain terminal acetylene starch. First, 20 mL of N,N-dimethylformamide was mixed with 40 mL of water. Then, 6 g of terminal acetylene starch and 260 mg of 3-azidopropylamine were dissolved in the mixed solution. 45 mg of copper sulfate pentahydrate and 45 mg of sodium ascorbate were added. The solution was stirred at 80 °C for 12 h. The product was dissolved in a mixture of 20 mL of dichloromethane and 20 mL of trifluoroacetic acid for protection. Stirring was continued at room temperature for 6 h under N2 flow. The solution was then dialyzed for 48 h and then dried to obtain terminal cationic starch.

4. The method for preparing simulated stone using chrome-containing leather ash as claimed in claim 3, starch waterproofing agent: 16g of hydroxypropyl starch and 14-17g of terminal cationic starch are weighed respectively, and a suspension with a concentration of 6% is prepared with deionized water and placed in a three-necked flask; the suspension is heated and kept warm for 2 h at 98°C in a constant temperature water bath with mechanical stirring to obtain a membrane liquid; 3g of hydroxysilicone oil is dissolved in 50mL of ethyl acetate and mixed with the membrane liquid, and the reaction is stirred at 70-80°C for 1-2h, and then 6g of water, 3-4g of coupling agent and 0.3-0.5g of 1-(3-chloropropoxy)-4-fluorobenzene are added, the pH is adjusted to 10, the reaction is stirred at 30-40°C for 1-2h, and vacuum dried to obtain a starch waterproofing agent.

5. The method for preparing simulated stone using chrome-containing leather ash as claimed in claim 4, wherein the coupling agent is KH550 and KH570.

Citation Information

Patent Citations

  • Method for manufacturing particle board by using chromium-containing leather-grinding ash

    CN110527305A

  • Hydroxy aluminium oxalate, and its preparing method and hydroxy aluminium oxalate as fire retardant

    CN1640865A

  • Method for preparing foamed concrete on basis of utilizing leather-making chromic leather meal and coal gangue

    CN110183155A

  • Particle board manufactured by using chromium-containing buffing dust and required substance thereof

    CN113025062A